Suppose 2*t - 2*p = -8, 16 = t + 2*p + 2*p. Suppose -3*n - n = t. Solve n*o + 4 = -o for o.
-4
Suppose 0 = -0*y - y + 3. Suppose -y*w = -5*w + 2*s, 3*w = -3*s + 6. Let r = 3 + w. Solve r*z - 12 - 4 = 0 for z.
4
Suppose 3*b + 5*o = 28, -2*b = -5*b + 3*o - 12. Let j(x) = 2*x. Let f be j(b). Solve f*p = -p for p.
0
Let q be 22⁄5 - 4⁄10. Let u = -17 + 17. Solve u = -q*o + 3*o for o.
0
Let k = -3 - -8. Suppose 0 = k*l + 4*s - 22, 7 - 20 = -2*l - 3*s. Solve -4*w = -3*w - l for w.
2
Suppose g = -1, 22 = -4*r - 3*g - 21. Let n(y) = -y3 - 10*y2 - y - 6. Let f be n®. Solve z = 5*z - f for z.
1
Let i be -1 + 7 - (-3 + 4). Suppose 2*c + 3*y - 2 - 5 = 0, 3*c - i = y. Suppose 0 = -q + c. Solve v = q*v for v.
0
Suppose 6*m - 19 - 17 = 0. Solve -m*d = -3*d for d.
0
Let h® be the second derivative of r5⁄20 - 5*r4⁄12 + r3⁄6 - 5*r2⁄2 - 5*r. Let f be h(5). Solve -16 = -f*q + 4*q for q.
-4
Let g = -76 + 52. Let k be 4/(-14) + g/14. Let y be (-1 - -2) + k + 3. Solve -y*t = -3 + 13 for t.
-5